(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines the phenomenon of emaciation (Nuhul) in classical Arabic Ghazal as a somatic embodiment of self-alienation, exploring its profound psychological and existential dimensions. The study traces the manifestations of this alienation across two primary sections: The first section investigates emaciation in relation to temporal alienation, manifested as a tethering to the past and a repudiation of the present. The second section explores emaciation and the alienation of death, wherein physical annihilation is transfigured into ultimate salvation. The research concludes that the dissolution of the flesh serves as an objective correlative to the immortality of passion—a proclamation of spiritual triumph and a symbolic union with the beloved that transcends the finitude of time and space.